2006
DOI: 10.1016/j.jcrs.2005.12.131
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopic analysis of acrylic intraocular lenses for microincision cataract surgery

Abstract: Visual results and long-term biocompatibility of the IOLs are influenced by surface properties. In recent years, there has been a trend toward microincision cataract surgery. Our study shows that the 2 IOL models now available for sub-2.0 mm microincision have acceptable surface properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…However, MICS IOLs have to fulfil special requirements concerning tolerance to high compression during the implantation process additionally to a good capsular bag stability and low PCO rates 9. The plate-haptic MICS IOL used in this study fulfilled these requirements concerning foldability, not showing any visible damage when injected with a special MICS injector 15. Furthermore, Prinz et al 16 showed that the MICS IOL used in our study was stable within the capsular bag concerning rotation, which is relevant for toric designs of this IOL.…”
Section: Discussionsupporting
confidence: 51%
“…However, MICS IOLs have to fulfil special requirements concerning tolerance to high compression during the implantation process additionally to a good capsular bag stability and low PCO rates 9. The plate-haptic MICS IOL used in this study fulfilled these requirements concerning foldability, not showing any visible damage when injected with a special MICS injector 15. Furthermore, Prinz et al 16 showed that the MICS IOL used in our study was stable within the capsular bag concerning rotation, which is relevant for toric designs of this IOL.…”
Section: Discussionsupporting
confidence: 51%
“…[16][17][18][19][20][21][22][23][24] Goldberg et al 25 advocate low-voltage SEM using minimal or no conducting surface coating to analyze IOL surfaces. However, until recently, the validity of SEM results has suffered because water-containing materials must be dehydrated for scanning, which deforms the specimen.…”
Section: Discussionmentioning
confidence: 99%
“…26 Furthermore, it is often necessary to enlarge the wound to approximately 2.0 mm for IOL insertion because IOLs that can be inserted through a sub-2.0 mm incision are still evolving. [27][28][29][30][31][32] In contrast, coaxial MICS can be performed with an incision of approximately 2.0 mm without wound enlargement for IOL insertion. Furthermore, the technique is easy to learn for most surgeons because it is almost the same as that for conventional SICS.…”
Section: J Cataract Refract Surg 2009; 35:233-239 Q 2009 Ascrs and Escrsmentioning
confidence: 99%